Analysis of the Reliability of Feather Sections for Corticosterone Measurement in Pekin Ducks - Se-Jin Lim; Chan Ho Kim; Ka Young Yang; Woo Do Lee; Su Mi Kim; Yang-Ho Choi; Jung Hwan Jeon (Animals)
The aim of this study was to identify the feather section, among the whole feather, rachis, and vane, with the highest reliability for corticosterone measurement in 10 Pekin ducks aged 42 days. In total, 60 samples (i.e., 20 per section) were collected and each section was analyzed in duplicate. Corticosterone levels were measured using ELISA and statistical analyses were performed using ANOVA in SAS 9.2, and the intra-class correlation coefficient (ICC) was tested using IBM SPSS. The level in the whole feather (12.55 ± 4.41 pg/mg) was significantly lower (p < 0.001) than that in the rachis (18.12 ± 5.70 pg/mg). No significant differences were observed between the rachis and the vane (20.40 ± 3.04 pg/mg). ANOVA results confirmed substantial hormonal variability depending on the feather part analyzed. The ICCs for the whole feather, rachis, and vane were 0.923, 0.876, and 0.004, respectively. The vane section exhibited the highest concentration and lowest variance, whereas the whole feather exhibited the highest ICC. Although the whole feather had the lowest concentration, it exhibited greater consistency. Further research is necessary to improve the feather corticosterone analysis method for more accurate analysis. In conclusion, the whole feather provides the most reliable measure of corticosterone concentration among the three parts.